Traces of the Rosary Confraternity, Albrecht Dürer, and Two Emperors in the Frescoes of the Church of St. Primus above Kamnik - Mija Oter Gorenčič (Acta Historiae Artis Slovenica, 2019)
The essay addresses the complex background of the origins of the high quality frescoes in the succursal church of St. Primus and Felician above Kamnik from the beginning of the 16th century. The author demonstrates that the frescoes were commissioned by the Marian Confraternity in Kamnik. The confraternity closely modeled the design and individual iconographic details on work commissioned by the renowned Rosary Brotherhood in Cologne or in close connection to it. That link is further supported by the Slovenians’ famous pilgrimages to that city, which can be traced from the 14th century onwards. The route to the Rhineland led them through Nuremberg, the town of Albrecht Dürer, whose influence can be recognized in stylistic characteristics of the frescoes. Furthermore, the association of Dürer with confraternities of the Rosary indicates the close interconnectedness of Rosary brotherhoods across Central Europe.